Uncontrolled Diabetes Mellitus during Lockdown period of Covid 19 pandemic - Mall, D. (Journal of Diabetes and Endocrinology Association of Nepal, 2023)
Background: Nepal Government had declared a lockdown from 24th March till 21st July 2020 for prevention and control of spread of Covid 19 pandemic. This has made patients with diabetes mellitus unable to do their physical activity outside home, not able to visit physicians or healthcare workers on time, buy medicines on time, check blood sugar as scheduled. In this study we aimed to study the effect of lockdown on glycemic control of Diabetes patients. Methods: This study was done at National Academy of Medical sciences, Bir Hospital-Endocrine Unit outpatients department. After the ease of lockdown certain patients visited us with past and new reports of Blood glucose and HbA1c. We kept a record of variation of glycemic control, lack of physical activities, continuation of medications and daily food habits. Results: Total of 91 Diabetes Mellitus patients visited our OPD in 3 weeks period after lockdown was eased. 58% were Female and 42 % were Male. Only 7% of patients had good control of Diabetes, 32% had fairly controlled Diabetes and 61% had poorly controlled Diabetes in males. In females 3% had good control of Diabetes, 27% had fairly controlled and 70% had poorly controlled Diabetes. 46-65 age group in both male and female had uncontrolled blood sugar. Among males 49% had increased food habits, 32% had decreased physical activity and 10% of them left or decreased medicine. In similar among females 23% had increased food habits, 39% decreased physical activity, 38% had left or decreased medicines. Conclusion: Lockdown during Covid 19 pandemic had adverse effect on glycemic control of patients. This will lead to further complications of diabetes mellitus. Patients must do normal physical activities. They can do normal exercise inside their house and increase activities with family members in a small area, where possible. We must advice our patients to learn how to perform self glucose monitoring and self adjustment of Insulin and diet. Learning how to access to physicians, healthcare workers and pharmacist through telemedicine is very important during lockdown period.